The political action and the violence’s stigma among postconflcit universities’ students: A study in the Universidad Nacional Mayor de San Marcos and the Universidad Nacional de San Cristóbal de Huamanga - Jave, Iris (2015)
This paper explores the different way on which the internal armedconflict still affects the Peruvian universities; now, through a process of symbolic violence from many spheres like the family or the mass media. In this context, the students build new forms of political participation; the university as a space of political debate and action is seriously affected by the fear of its students to be marked by the stigma of the violence; moreover, all this is amplified by the destruction of the political system and the lack of interest on the regular ways of political participation among young students. Although, in our research we have found that university students participate in different spheres of the public life that, without being planned, cre- ates new ways of political participation: the case of the colectivos. We conclude that between the stigma —and the supposed presence of Movadef in the universities—, and the lack of institutional ways to channel their demands, the students are building a new form of political action that will be fully shaped in the future when they achieve to structure their movement and colectivos.